2009
DOI: 10.1073/pnas.0813164106
|View full text |Cite
|
Sign up to set email alerts
|

A molecular brake, not a clutch, stops the Rhodobacter sphaeroides flagellar motor

Abstract: Many bacterial species swim by employing ion-driven molecular motors that power the rotation of helical filaments. Signals are transmitted to the motor from the external environment via the chemotaxis pathway. In bidirectional motors, the binding of phosphorylated CheY (CheY-P) to the motor is presumed to instigate conformational changes that result in a different rotor-stator interface, resulting in rotation in the alternative direction. Controlling when this switch occurs enables bacteria to accumulate in ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
78
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(81 citation statements)
references
References 34 publications
2
78
1
Order By: Relevance
“…This model of motion is applicable to many species that are amenable to study using tracking methods. Examples include bacteria such as R. sphaeroides that reorient by stopping the rotation of their flagellum [31], flying insects that pause on landing sites [14] and ruminants that pause at foraging sites [4,17]. We demonstrated that the inclusion of stationary phases in the underlying motion leads to complex variation in the observed standard deviation of RASs, and suggested an explanation based on consideration of the evolution of the RAS pdf.…”
Section: Discussionmentioning
confidence: 99%
“…This model of motion is applicable to many species that are amenable to study using tracking methods. Examples include bacteria such as R. sphaeroides that reorient by stopping the rotation of their flagellum [31], flying insects that pause on landing sites [14] and ruminants that pause at foraging sites [4,17]. We demonstrated that the inclusion of stationary phases in the underlying motion leads to complex variation in the observed standard deviation of RASs, and suggested an explanation based on consideration of the evolution of the RAS pdf.…”
Section: Discussionmentioning
confidence: 99%
“…For BFM experiments flagellar filaments were truncated by passing a bacterial suspension through two syringes with narrow gauge needles (26G) connected with a plastic tube ('shearing device' [Bai et al, 2010, Pilizota et al, 2009). Subsequently, cells with truncated filaments were washed by centrifugation.…”
Section: Sample Preparation and Osmotic Shockmentioning
confidence: 99%
“…Subsequently, cells with truncated filaments were washed by centrifugation. Slides for BFM experiments were prepared as before [Bai et al, 2010, Pilizota et al, 2009] by layering two parallel strips of double sided sticky tape onto a microscope slide and covering them with a cover glass, forming a tunnel slide (SI Appendix Fig. 5) of approximate volume of ∼ 8 µl.…”
Section: Sample Preparation and Osmotic Shockmentioning
confidence: 99%
“…The observation of such a fine stepping motion was made possible by reducing the number of functional stators in the sodium ion-driven chimeric flagellar motor and lowering sodium ion motive force to reduce the rotation rate to meet the spatial and temporal resolution of the measurement system (20). It has also been reported that the unidirectional motor of Rhodobacter sphaeroides stops at 27-28 discrete angles, locked in place by a relatively high torque (19). Interestingly, backward CW steps of the sodium ion-driven chimeric flagellar motor were also often observed even in the absence of CheY, but the step size (−10.3°) was slightly smaller than the forward CCW steps (13.8°) (20), suggesting an asymmetric mechanism of bidirectional rotation.…”
mentioning
confidence: 99%
“…Recently, it has been reported that the c-di-GMP binding protein YcgR binds to MotA, FliG, and FliM in the presence of c-di-GMP, resulting not only in a reduced motor speed but also in the CCW bias in motor rotation (3,4). In Rhodobacter sphaeroides, the flagellar motor rotation is unidirectional, but CheY-P acts as a molecular brake to stop motor rotation to change the swimming direction (19).…”
mentioning
confidence: 99%